COVID-19 as a Family Stressor: A Life Course Exploration of Family Stress Among Rural Grandparents and Their Adult Children in Upstate New York - Obernesser, Laura (Qualitative Sociology Review, 2025)
COVID-19 has brought about many changes for rural families, affecting their family roles, childcare responsibilities, financial status, and experiences of family stress. In this study, I examine (1) how rural grandparents and their adult children perceive family stress related to their family roles and responsibilities during COVID-19 and (2) how rural grandparents and their adult children have coped with the stress of family roles and responsibilities during COVID-19. Data comes from 44 in-depth interviews. The findings of this study suggest that COVID-19, a family stressor, has been the source of stress among rural grandparents and their adult children. The findings suggest that families adapted through a range of improvised strategies such as relocating, abstaining from employment, taking on additional childcare, and adjusting personal identities to maintain stability during uncertainty. These adaptations were not merely practical but often guided by moral and faith-based reasoning, allowing participants to maintain agency despite constraints. Before the COVID-19 pandemic, grandparents played a significant role in childcare, sometimes to the point of being the primary childcare providers (Harrington Meyer 2014). COVID-19 has further complicated the roles and responsibilities of rural grandparents and their adult children. COVID-19 brought changes to rural families, particularly in the areas of their employment, family roles and relationships, childcare responsibilities, and sense of hope.